Answer:
x=-12
Step-by-step explanation:
3x+5=2x-7
3x=2x-12
x=-12
Answer:
Step-by-step explanation:
f(x) = x + 2.....change f(x) to y
y = x + 2....now switch x and y and solve for y
x = y + 2
x - 2 = y....change y to f-1(x)...represents an inverse
f-1(x) = x - 2 <== ur inverse
Answer:
29: A
30: $7.50
31: number of dots in total:
1) 0 dots
2) 1 dot
3) 1 dot
4) 3 dots
5) 1 dot
6) 1 dot
7) 1 dot
8) 0 dots
Step-by-step explanation:
Y= -10x + 190
In using a linear function, follow the pattern y=mx + b.
In this scenario, the m (which represents slope) is -10 since $10 is taken away every time. The b(which represents y-int) is 190 because you start with 190 (x=0)
Formula= (y2-y1)/ (x2-x1)
(-5 - -1) / (-2 - -4)
(-4) / (2) = -2
q8 is C
(-3 - -3) / (8 - 4)
(0) / (4) = 0
q12 is D